Mouse model of panic disorder: Vulnerability to early environmental instability is strain‐dependent. Issue 6 (1st July 2021) - Luchetti, Alessandra; Di Segni, Matteo; Andolina, Diego; Ventura, Rossella; Battaglia, Marco; D'Amato, Francesca Romana
Abstract: Early life experiences and genetic background shape phenotypic variation. Several mouse models based on early treatments have evaluated short‐ and long‐term phenotypic alterations and explored their molecular mechanisms. The instability of maternal cues was used to model human separation anxiety in outbred mice, one of the etiopathogenetic factors that predict panic disorder (PD). Application of the repeated cross‐fostering (RCF) protocol to inbred strains (C57 and DBA) allowed us to measure differential responses to the same experimental manipulation. Ultrasounds emitted during isolation indicated that after RCF, pups from both strains lose their ability to be comforted by nest cues, but the frequency modulation of separation calls increased in RCF‐C57 and decreased in RCF‐DBA mice. No strain‐specific difference in olfactory ability explained these responses in RCF‐exposed mice. Rather, disruption of the infant‐mother bond may differentially affect separation calls in the two strains. Moreover, the RCF‐associated increased respiratory response to hypercapnia–an endophenotype of human PD documented among mice outbred strains–was replicated in the C57 strain only. We suggest that RCF‐induced instability of the early environment affects emotionality and respiratory physiology differentially, depending on pups' genetic background. These strain‐specific responses provide a lead to understand differential vulnerability to emotional disorders.